2017
DOI: 10.1002/jmv.24950
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes in liver stiffness and controlled attenuation parameter following direct‐acting antiviral therapy against hepatitis C virus genotype 1b

Abstract: Little information is available on the impact of direct-acting antiviral (DAA) therapy on changes in liver fibrosis and steatosis. Liver stiffness (LS) and controlled attenuation parameter (CAP) values were evaluated using transient elastography. The study subjects were 214 elderly patients infected with HCV genotype 1b who received 24-week daclatasvir and asunaprevir dual therapy. All patients of this retrospective study had no hepatocellular carcinoma before and during DAA therapy. LS and CAP were assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 29 publications
8
50
0
1
Order By: Relevance
“…Other studies, carried out in patients with advanced cirrhosis and portal hypertension, have shown that obtaining a SVR to DAA treatment determines a meaningful reduction in hepatic venous pressure gradient, thus portending a future decrease in the development of complications of liver disease as well as an improvement in patients prognosis . More recently, some studies carried out primarily in Eastern countries, with limited follow‐up, and inclusion of heterogeneous cohorts of patients in terms of both disease severity and aetiology, consistently observed that even in HCV patients with less advanced liver disease, measurement of liver stiffness and assessment of other noninvasive indices of liver fibrosis tend to ameliorate in a relatively short‐term follow‐up after SVR …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies, carried out in patients with advanced cirrhosis and portal hypertension, have shown that obtaining a SVR to DAA treatment determines a meaningful reduction in hepatic venous pressure gradient, thus portending a future decrease in the development of complications of liver disease as well as an improvement in patients prognosis . More recently, some studies carried out primarily in Eastern countries, with limited follow‐up, and inclusion of heterogeneous cohorts of patients in terms of both disease severity and aetiology, consistently observed that even in HCV patients with less advanced liver disease, measurement of liver stiffness and assessment of other noninvasive indices of liver fibrosis tend to ameliorate in a relatively short‐term follow‐up after SVR …”
Section: Discussionsupporting
confidence: 92%
“…11,12,15 More recently, some studies carried out primarily in Eastern countries, with limited follow-up, and inclusion of heterogeneous cohorts of patients in terms of both disease severity and aetiology, consistently observed that even in HCV patients with less advanced liver disease, measurement of liver stiffness and assessment of other noninvasive indices of liver fibrosis tend to ameliorate in a relatively short-term follow-up after SVR. 16,21 In the current study, our aim was to assess the modifications in liver stiffness, as an indirect measure of liver fibrosis, and of biochemical, noninvasive indices of liver disease severity (ie, APRI score, FIB-4 score) as well as of clinical and instrumental parameters suggestive of portal hypertension (ie, thrombocytopenia, splenomegaly) in a series of patients with advanced, compensated liver disease due to HCV infection who had obtained a SVR to DAA treatment and who had a follow-up after the end of treatment of at least 1 year. Under these conditions, we observed that obtaining a SVR is associated with a significant decrease in liver stiffness, as measured by transient elastography, and that although this decrease is proportionally more pronounced in cirrhotic patients as compared to patients with advanced fibrosis (−44.1% vs −36.4%), a decrease in at least one METAVIR stage-as assessed by liver stiffness measurement-is more frequently observed in F3 patients (76.0%) as compared to F4 patients (44.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most of the improvement in FIB‐4 or APRI occurred in the first 6 months of follow‐up (data that are consistent with results from a recent study of 111 patients with serial liver stiffness measurements following SVR) . The rapidity of this improvement suggests that the observed change likely reflected improvement in the necro‐inflammatory component rather than fibrosis stage per se .…”
Section: Discussionsupporting
confidence: 89%
“…It can also provide prognostic information during the post-treatment follow-up [20,21]. Some recent studies confirmed higher diagnostic value of SWE compared to TE, and therefore we applied this technique in our practice and in this study [22,23].…”
Section: Introductionmentioning
confidence: 84%